2007
DOI: 10.1242/dev.010272
|View full text |Cite
|
Sign up to set email alerts
|

Lrp6 is required for convergent extension duringXenopusgastrulation

Abstract: *Wnt signaling regulates ␤-catenin-mediated gene transcription and planar cell polarity (PCP). The Wnt co-receptor, Lrp6, is required for signaling along the ␤-catenin arm. We show that Lrp6 downregulation (by morpholino injection) or overexpression in Xenopus embryos disrupts convergent extension, a hallmark feature of Wnt/PCP components. In embryos with decreased Lrp6 levels, cells of the dorsal marginal zone (DMZ), which undergoes extensive cellular rearrangements during gastrulation, exhibit decreased leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 48 publications
(52 reference statements)
2
65
0
1
Order By: Relevance
“…Among these genes, Fzds and Dvls also act upstream of β-catenin in the canonical Wnt pathway. In addition, Lrp6, a Wnt co-receptor acting upstream of β-catenin and also involved in convergent extension, is required for neural tube closure and caudal axis elongation (Carter et al, 2005;Kokubu et al, 2004;Pinson et al, 2000;Tahinci et al, 2007;Zhou et al, 2010). Although we did not detect significant alterations in representative PCP signaling gene expression patterns in the conditional β-catenin mutants, future studies are needed to examine whether PCP signaling functions are indirectly altered in β-catenin signaling mutants or whether β-catenin signaling is altered and contributes to NTDs in the PCP signaling mutants, including mutants of Fzds and Dvls.…”
Section: Co-regulation Of Cdx2 By β-Catenin and Pax3 During Neurulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these genes, Fzds and Dvls also act upstream of β-catenin in the canonical Wnt pathway. In addition, Lrp6, a Wnt co-receptor acting upstream of β-catenin and also involved in convergent extension, is required for neural tube closure and caudal axis elongation (Carter et al, 2005;Kokubu et al, 2004;Pinson et al, 2000;Tahinci et al, 2007;Zhou et al, 2010). Although we did not detect significant alterations in representative PCP signaling gene expression patterns in the conditional β-catenin mutants, future studies are needed to examine whether PCP signaling functions are indirectly altered in β-catenin signaling mutants or whether β-catenin signaling is altered and contributes to NTDs in the PCP signaling mutants, including mutants of Fzds and Dvls.…”
Section: Co-regulation Of Cdx2 By β-Catenin and Pax3 During Neurulationmentioning
confidence: 99%
“…In addition, Lrp6 is a key co-receptor in the canonical Wnt pathway and is required for a wide range of organogenetic events, including neural tube closure in mice (Carter et al, 2005;Kokubu et al, 2004;Mao et al, 2001;Pinson et al, 2000;Song et al, 2009;Song et al, 2010;Tamai et al, 2000;Wehrli et al, 2000;Zhou et al, 2008;Zhou et al, 2004;Zhou et al, 2010). However, Lrp6 is also implicated in convergent extension during Xenopus gastrulation (Tahinci et al, 2007) and may mediate non-canonical Wnt signaling for neural tube closure (Gray et al, 2013). Thus, the role of canonical Wnt signaling, and especially of β-catenin, in neural tube closure and NTDs remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, maternal Wnt/b-catenin signaling specifies the organizer in Xenopus, chicken and zebrafish (Heasman et al, 1994;Roeser et al, 1999;Kelly et al, 2000;Oelgeschläger et al, 2003), whereas BMP signaling is required in mouse extraembryonic tissues for gastrulation and mesoderm formation (Kishigami and Mishina, 2005). Furthermore, roles for Wnt signaling are conserved in the regulation of the gastrulation process itself (Caneparo et al, 2007;Tahinci et al, 2007) and during specific cell and organ differentiation events (Nejak-Bowen and Monga, 2008;Thomas and Erickson, 2008). Thus, it is difficult to untangle the roles of Wnt and BMP signaling in axis specification from those in other processes.…”
Section: + +mentioning
confidence: 99%
“…Therefore, in current models of PCP in flies, JNK is no longer considered to play a key role in PCP signaling. The role of JNK in mammalian PCP is generally accepted (Bloor and Kiehart 2002;Kaltschmidt et al 2002;Kuhl 2002;Schwarz-Romond et al 2002;Habas et al 2003;Takeuchi et al 2003;Cong et al 2004;Medina et al 2004;Unterseher et al 2004;Schambony and Wedlich 2007;Tahinci et al 2007;Bikkavilli et al 2008), although some recent studies have suggested that inhibiting JNK either genetically or with pharmacological inhibitors does not affect convergent extension (Ybot-Gonzalez et al 2007). In any case, the exact contribution of JNK to mammalian PCP is not yet clear and requires further investigation.…”
Section: Vertebrate-specific Pcp Genesmentioning
confidence: 99%